Mu-opioid receptors in nociceptive afferents produce a sustained suppression of hyperalgesia in chronic pain. Issue 8 (August 2018) - Severino, Amie; Chen, Wenling; Hakimian, Joshua K.; Kieffer, Brigitte L.; Gaveriaux-Ruff, Claire; Walwyn, Wendy; Marvizón, Juan Carlos G.
Abstract : Abstract: The latent sensitization model of chronic pain reveals that recovery from some types of long-term hyperalgesia is an altered state in which nociceptive sensitization persists but is suppressed by the ongoing activity of analgesic receptors such as μ-opioid receptors (MORs). To determine whether these MORs are the ones present in nociceptive afferents, we bred mice expressing Cre-recombinase under the Nav 1.8 channel promoter (Nav 1.8cre) with MOR-floxed mice (flMOR). These Nav 1.8cre/flMOR mice had reduced MOR expression in primary afferents, as revealed by quantitative PCR, in situ hybridization, and immunofluorescence colocalization with the neuropeptide calcitonin gene-related peptide. We then studied the recovery from chronic pain of these mice and their flMOR littermates. When Nav 1.8cre/flMOR mice were injected in the paw with complete Freund adjuvant they developed mechanical hyperalgesia that persisted for more than 2 months, whereas the responses of flMOR mice returned to baseline after 3 weeks. We then used the inverse agonist naltrexone to assess ongoing MOR activity. Naltrexone produced a robust reinstatement of hyperalgesia in control flMOR mice, but produced no effect in the Nav 1.8/flMOR males and a weak reinstatement of hyperalgesia in Nav 1.8/flMOR females. Naltrexone also reinstated swelling of the hind paw in flMOR mice and female Nav 1.8cre/flMOR mice, but not male Nav 1.8cre/flMOR mice. The MOR agonist DAMGO inhibited substance P release in flMOR mice but not Nav 1.8cre/flMOR mice, demonstrating a loss of MOR function at the central terminals of primary afferents. We conclude that MORs in nociceptive afferents mediate an ongoing suppression of hyperalgesia to produce remission from chronic pain. Abstract : Selective knockout of µ-opioid receptors in nociceptive primary afferents shows that they continually suppress hyperalgesia in the latent sensitization model of chronic pain.